Measurement of Electrokinetically induced hydrodynamics at Ion-selective interfaces using 3D Micro particle tracking velocimetry (µPTV) - Felix Stockmeier; Michael Schatz; Malte Habermann; John Linkhorst; Ali Mani; Matthias Wessling (MethodsX, 2022)
ABSTRACT: Electrokinetic flow phenomena are ubiquitous in electrical systems for desalination, chemical conversion, or mixing at a micro-scale. However, the important features of resulting 3D flow fields are only accessible through cost-intensive numerical simulations. Experimental 2D recording of the chaotic three-dimensional velocity fields developing for example at currents exceeding the limiting current density does not capture the complex 3D structures present in such flow fields. Additionally, numerical 3D studies are limited to dimensions three orders of magnitude smaller as found in real applications and only short run times due to the enormous computational effort. To apply the theoretical knowledge in real-world systems and create the possibility for detailed parameter studies, we present the first experimental method for recording and quantifying the time-resolved velocity field in an electrochemical microfluidic cell in 3D with dimensions found in industrial applications. We utilize this method in a co-submitted paper to record the 3D velocity field of electroconvection at a cation-exchange membrane. • Cell design suitable for simultaneous electrochemical experiments with optical 3D velocity quantification • Method optimized for velocity reconstruction of membrane-to-membrane distances found in industrial cells • Highly adaptable cell design, for optical characterization of electrochemical systems